A CASE REPORT ON CONGENITAL LOBAR EMPHYSEMA - Unnikrishnan, Karthika; Kn, Anila (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Congenital lobar emphysema (CLE) disorder is an uncommon respiratory issue in which air can enter the lungs yet cannot escape, bringing about over inflation (hyperinflation) of the projections of the lung with an incidence 1 per 20,000-30,000 per birth. It is frequently recognized in babies or youthful newborn children; however, a few cases do not get to be distinctly evident until adulthood. This issue might be sufficiently serious to bring about related heart issues. We report a case of a 1-month-old female infant who showed the signs and symptoms of this disease, but responded well to her treatment and was discharged in a stable state. Â 